Future Architecture Sustainability through Green Design Principle in Sade Vernancular Settlement - Fidelista, Alya Nafisa; Nugroho, Agung Murti; Novianto, Bagus Fajar; Savitri, Diana; Ramadhan, Muhammad Hafizh; Muhammad, Infaroyya Al Karimah (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2026)
Climate change poses pressing design and environmental challenges, addressable through time-tested vernacular architecture. The Sade settlement on Lombok exemplifies enduring green design practices worth examining for modern applications. This study employs a systematic literature-based methodology: reviewing green architecture benchmarks for an overview; analyzing studies on Sade Village's physical forms; identifying links between general green criteria and local implementations; and formulating principles for future general and vernacular architecture. Using descriptive-evaluative methods, it assesses design elements against eco-friendly standards. Key findings reveal Sade's strengths, including compact, contour-parallel building masses with linear circulation; north-south orientation for optimal passive lighting and ventilation; regulated heights with lightweight, hollow local materials for humid tropical and seismic resilience; ample green open spaces to counter urban heat islands; and nature-responsive site utilities. These principles demonstrate adaptive, ecosystem-sustaining design. The research yields actionable recommendations for integrating such green design principles into future architecture, particularly preserving and enhancing them in Sade and similar vernacular contexts to support long-term environmental sustainability.